2022
DOI: 10.1111/cts.13438
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to polypharmacy and hyper‐polypharmacy for the elderly: A nationwide cohort study using National Health Insurance data in South Korea

Abstract: Polypharmacy may cause adverse health outcomes in the elderly. This study examined the prevalence of continuous polypharmacy and hyper‐polypharmacy, factors associated with polypharmacy, and the most frequently prescribed medications among older adults in South Korea. This was a retrospective observational study using National Health Insurance claims data. In total, 7,358,953 Korean elderly patients aged 65 years and older were included. Continuous polypharmacy and hyper‐polypharmacy were defined as the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 62 publications
2
15
1
2
Order By: Relevance
“…Cho and colleagues found that nearly half of the elderly South Korean patients had PP and the combinations of cardiovascular, anti-lipidemic and acid-suppressing drugs were most commonly prescribed. 4 Based on these evidences, there has been the global trend towards more and more perplexed prescriptions of the drug classes affecting or modulating cardiovascular and nervous systems representing the burdens of non-communicable diseases (NCDs) in the ageing society emerging in many parts of the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cho and colleagues found that nearly half of the elderly South Korean patients had PP and the combinations of cardiovascular, anti-lipidemic and acid-suppressing drugs were most commonly prescribed. 4 Based on these evidences, there has been the global trend towards more and more perplexed prescriptions of the drug classes affecting or modulating cardiovascular and nervous systems representing the burdens of non-communicable diseases (NCDs) in the ageing society emerging in many parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs for acid-related disorders were most commonly prescribed. 4 Depending on the de nition of polypharmacy, 11-96% of the elderly cancer patients were subjected to be exposed too many concurrent medications. 5 Jörgensen, et al conducted a population-based case-control study to explore pattern of drug uses among Danish cancer patients and found that at cancer diagnosis, 35% of elderly cancer patients used more than 5 drugs daily compared with 27% of controls.…”
Section: Introductionmentioning
confidence: 99%
“…In a South Korean review of 7.36 million patients in the National Health Insurance claims database, 36.9% of patients over the age of 65 used ≥ 5 prescription medications, while 7.1% used 10 or more medications. 2 In the United States, examination of the National Ambulatory Medical Care Survey revealed a point prevalence of polypharmacy ( ≥ 5 medications) of 44% in community-dwelling patients 65 years or older who did not have dementia, and 72% in those who did have dementia. 3 In a Danish population, the broader issues of potentially inappropriate medication (PIM) use was examined through a population-based register.…”
mentioning
confidence: 99%
“…4 While the term polypharmacy indicates the administration of multiple medications in a patient, there is no consensus definition. A systematic review of polypharmacy definitions categorized them as "(1) numerical only (using the number of medications to define polypharmacy), (2) numerical with an associated duration of therapy or health care setting (such as during hospital stay), or (3) descriptive (using a brief description to define polypharmacy)." 5 Additional terms may also be associated with the definition, such as minor, major, chronic, or hyper-polypharmacy.…”
mentioning
confidence: 99%
See 1 more Smart Citation